Disparity Knowledge and Implementation Postpartum Depression Policy at RSJ Mutiara Sukma Mataram - Shindy Fajriani Fasha; Sastrawan (Postgraduate, University of Mataram, 2025)
Postpartum depression remains a significant mental health problem, with policies not yet adequately implemented in healthcare practice. Postpartum depression can disrupt children's growth and development, cause pain and disability, and make it difficult for them to meet their needs. Postpartum depression (PPD) is a mental health condition experienced by mothers after childbirth, which can negatively impact the mother, baby, and family. Current policies for managing PPP still adhere to the general PPP policy. The purpose of this study was to determine the disparity between knowledge and implementation of postpartum depression management policies at Mutiara Sukma Mental Hospital, Mataram. The research method was descriptive quantitative, and this study involved 32 respondents, including nurses and management staff. Data were collected through a structured questionnaire and analyzed using univariate statistics. The results showed that 62.5% of respondents were unaware of the policy, 65.6% had not implemented it in clinical practice, and 43.8% faced challenges during implementation. These findings reflect a gap between policy design and field application. The implementation of policies related to PPP is ineffective and requires strategic intervention by hospital management and healthcare professionals. The conclusion is that the disparity between knowledge and implementation of postpartum depression management policies at Mutiara Sukma Mental Hospital, Mataram, is still lacking, so special training is needed for health workers.